Evaluasi Kebijakan Perda No. 4 Tahun 2013 Tentang Penanggulangan HIV/AIDS di Kota Surabaya (Kajian Terhadap KPA (Komisi Penanggulangan AIDS) dan data kasus HIV/AIDS tahun 2010 s/d 2014 di Kota Surabaya) - Dendy Guswantoro (DIA: Jurnal Administrasi Publik, 2014)
AIDS Commission (KPA) noted that the East Java city of Surabaya is still ranked first number of HIV AIDS in East Java. In connection with this, then in order to provide legal certainty and protection against any efforts to combat HIV and AIDS in Surabaya established Regulation No. 4 Year 2013 on HIV and AIDS. In this study used qualitative research methods and evaluation methods used "Before and After Comparasions" so that the evaluation process by comparing the data of cases of HIV / AIDS in Surabaya from 2010 till 2014 the condition of case data before and after the policy is implemented regulations. Strategy or focus of the work program KPA as a commission appointed in efforts to prevent and control HIV / AIDS, currently only focuses on the patient only (OHDA) and community groups both the profession and the environment prone to HIV transmission. This is contrary to the legislative text. The level of success of the implementation of Regulation No. 4 in 2013 is still very much in doubt or can be said to be unsuccessful. The establishment of legislation and its implementation assessed not much influence. Data HIV / AIDS cases were discovered during the period of the year is contrary to the government's efforts Surabaya in HIV / AIDS by issuing Regulation No. 4 in 2013. KPA should be able to be a separate organizational structure with an arrangement of more detailed sub- structure and focus . Employment patterns and job description based on operating procedures are standardized (standard operating procedure or SOP ) of each part can be made more complex but not too long and more directly with the responsibilities that can be measured, so it can be better controlled and effective and seriousness in handling HIV / AIDS cases in the city of Surabaya can be seen. Strategy or focus of the work program of the government, especially the KPA should not only focus on the patient only (OHDA) and community groups both the profession and the environment vulnerable to HIV infection , but it can also focus on efforts to combat HIV/ AIDS in all societies with no social status, profession, age and risk factors.Keywords : Evaluation, settlement of HIV / AIDS, KPA (Komisi Penanggulangan AIDS)